Subjects of Interpretation: Second Language Acquisition by Jesuit Missionaries among the Northern Ojibwa, 1842–1880 - Parent, Gabrielle (Journal of the Canadian Historical Association / Revue de la Société historique du Canada, 2010)
This article focuses on second-language learning and “linguicide” in Upper Canada between 1843 and 1877. From the small group of Jesuits that made up the ranks of the Society of Jesus’ new missions to Canada in the post-suppression era, it was Jean Pierre Choné, Joseph Hanipaux, Nicholas Frémiot, and Dominique du Ranquet, August Kohler, Nicolas Point, and Joseph Jennesseaux that first learned Algonquin languages in order to proselytize to the Northern Ojibwa populations at the Upper Canada. The Upper Canada mission, led by superior Pierre Chazelle, re-established some of the Society of Jesus’ older Aboriginal missions, and expanded their evangelical territory north and west along Lake Huron and Lake Superior. Important stations were built among the Ojibwa at Wikwemikong on Manitoulin Island in 1844, in Sault Sainte Marie in 1846, and along the Pigeon and Kamanistikwa Rivers, near Fort William, in 1848. This paper examines why the new Jesuits were motivated to learn the languages spoken at their Aboriginal missions in the nineteenth century and simultaneously investigates how the massive and unexpected psychological challenges of the 1800s, including anti-Catholicism, British rule, mass immigration, and formidable industrial development in Upper Canada, supported or discouraged the Jesuits’ language acquisition.